Case Report: Targeted Therapy for Metastatic Solid Pseudopapillary Neoplasm of the Pancreas With CTNNB1 and PTEN Mutations - Wang, Xinbo; Zhu, Daojun; Bao, Wei; Li, Min; Wang, Sizhen; Shen, Rongxi (Frontiers in Oncology, 2021)
Background: Solid pseudopapillary neoplasm (SPN) of the pancreas shows an indolent clinical behavior in cases undergoing surgical resection. The efficacy of combination therapy in the metastatic extrapancreatic SPN treatment remains largely unknown and a clinical challenge. Case Presentation: We report a case of a metastatic pancreatic SPN in a 45-year-old woman who presented with an aggressive peritoneal dissemination and hepatic metastases and still showed an indolent clinical course with combination therapy with repeated surgery and targeted therapy. Although the follow-up effect remains to be seen, this is the first report of practical experience of the targeted agents sunitinib and everolimus in metastatic SPN tumors based on the mutation status of PTEN (c.379G>A; p.G127R) and CTNNB1 (c.98C>G; p.S33C). To our knowledge, the PTEN variant identified in this case has not been previously reported in SPN. Conclusion: Evidence on variant genetics indicates that future molecular studies may not only help to explain the mechanism of SPN occurrence and development but are also more likely to direct to future precision treatments.